The New Role of the Private Sector in Community Development: A Case Study in Artisanal Fishery Communities in Thailand - Kamnoonwatana, Nawat; Wongamphaiwit, Orada; Asvanund, Atip (European Journal of Sustainable Development, 2018)
Private sector’s role in community development is often seen as a supporting organization with its own interests. Generally, a company chooses to support a particular community according to the company’s strategic topic. This top-down approach benefits the company in many ways including effective operations and communications. However, the effectiveness on sustainable development of communities is still questionable. As each strategic topic is heavily influenced by the company’s reasoning, this approach often lacks in dimensions, has narrow focus, and therefore disconnects with the community real needs. This results in little contributions to the sustainability of the communities. This proposal proposes a different approach through a case study with two artisanal fishery communities. With this new approach, the company acted as a bridging organization working closely with the communities together with other stakeholders to truly understand their needs. The company, then, facilitated them in designing and implementing their own sustainable solutions. This requires changes in the company operations as well as acquiring new knowledge for its outreach team. The findings demonstrated a successful case of community development towards self-sustainable resource management. The analysis of these findings helps the company to strike a balance between “company-centric” and “community-centric” approach in the future.